Cover Feature: Elucidating the Performance Limitations of Alkaline Electrolyte Membrane Electrolysis: Dominance of Anion Concentration in Membrane Electrode Assembly (ChemElectroChem 19/2020). Issue 19 (31st August 2020) - Razmjooei, Fatemeh; Farooqui, Azharuddin; Reissner, Regine; Gago, Aldo Saul; Ansar, Syed Asif; Friedrich, Kaspar Andreas
Abstract : The Cover Feature illustrates the fabrication of a perovskite solar cell (PSC) based on lead fixation from an electrolyte as an electrodeposited PbO2 film, which is further converted to PbBr2 using gaseous HBr. Finally, PbBr2 is converted into CsPbBr3 using spin‐coated CsBr. A pressed carbon tip with a calibrated area was used to close the circuit in the PSC. This method avoids the spill of toxic lead compounds compared with traditional spin‐coating. More information can be found in the Article by D. Ramírez et al .